2015
DOI: 10.1051/matecconf/20152301057
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research of solid waste drying in the process of thermal processing

Abstract: Abstract. The convective drying process of municipal solid waste layer as a polydispersed multicomponent porous structure is studied. On the base of the experimental data criterial equations for calculating heat transfer and mass transfer processes in the layer, depending on the humidity of the material, the speed of the drying agent and the layer height are obtained. These solutions are used in the thermal design of reactors for the thermal processing of multicomponent organic waste.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…This drying method could provide faster drying efficiency in a shorter time as compared to other drying methods. With this drying method, 100% moisture reduction could be achieved, allowing 87% weight reduction and 70% volume reduction during the drying period of 6-10 h [74]. Among the different drying methods, biostabilization process takes the longest period, but it could reduce the weight of MSW by 85% in 100 d, as stated by He et al [46].…”
Section: Comparison Of Drying Methods Based On Dryingmentioning
confidence: 97%
See 1 more Smart Citation
“…This drying method could provide faster drying efficiency in a shorter time as compared to other drying methods. With this drying method, 100% moisture reduction could be achieved, allowing 87% weight reduction and 70% volume reduction during the drying period of 6-10 h [74]. Among the different drying methods, biostabilization process takes the longest period, but it could reduce the weight of MSW by 85% in 100 d, as stated by He et al [46].…”
Section: Comparison Of Drying Methods Based On Dryingmentioning
confidence: 97%
“…Bukhmirov et al [74] conducted the research on the convective thermal drying process at 0.1 meters per second of hot air flow rates in an experimental scale. Bukhmirov et al reported that about 100% of moisture reduction in MSW were achieved at drying temperature of 107-167°C during 160-260 min.…”
Section: Thermal Dryingmentioning
confidence: 99%